Analysis of the COVID-19 pandemic and prediction with numerical methods - M. M. Singh; D. L. Suthar; G. Agarwal; S. D. Purohit (International Journal of Mathematics for Industry)
Coronavirus spreads worldwide with various symptoms and strains such as COVID-19, SARS, MERS. Outbreak and prevention of the coronavirus can be studied by many mathematical models like SIR, SEIR and SEIQDR. In this paper, we employed Euler’s method based on the SEIQDR mathematical model of COVID-19. Also, after certain iterations of the population categories, we obtained the solution range of the SEIQDR model. In the end, we studied the impact of [Formula: see text] for integer 1 and fractional order 0.9 and 0.85 on the obtained numerical solutions. The graphical solutions are also analyzed for integer and fractional values of [Formula: see text]. The advantage of this proposed method is that it reduces the mathematical and numerical computations significantly and the proposed method is effective and efficient in extracting the approximate solution of various population categories for COVID-19 mathematical model.